2022
DOI: 10.3390/clockssleep4010008
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sleep and Circadian Rhythms for Vaccination Success and Susceptibility to Viral Infections

Abstract: Sleep and circadian rhythms are closely involved in the immune system and its regulation. Here, we describe this relationship and provide recommendations regarding the influence of sleep and circadian rhythms on vaccination success. We review studies investigating how viral susceptibility is influenced by changes in immunological parameters as a consequence of sleep deprivation. Short sleep duration and poor sleep efficiency both appear to be strong factors leading to greater vulnerability. In addition, both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Nowadays sleep-related problems and disruptions to normal circadian regulation are common. With the following research, it's been also shown that circadian rhythms and sleep are correlated with the participation of immunological function to it [9]. Less sleep makes people tired and with low performance those people have 7 -8 hours daily sleep.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Nowadays sleep-related problems and disruptions to normal circadian regulation are common. With the following research, it's been also shown that circadian rhythms and sleep are correlated with the participation of immunological function to it [9]. Less sleep makes people tired and with low performance those people have 7 -8 hours daily sleep.…”
mentioning
confidence: 91%
“…Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted:(REM) sleep [10]. Under ordinary conditions, rest and the circadian mood guarantee a mitigating state during the daytime and a pro-inflammatory state during the evening [9]. Intense gentle resistant enactment increases NREM state of sleep and smothers REM state of sleep, though serious invulnerable reaction with an upsurge of cytokine levels causes rest aggravation with the concealment of both NREM and REM state of sleep [11].…”
mentioning
confidence: 99%
“…sleep-related problems and disruptions to normal circadian regulation are common. With the following research, it's been also shown that circadian rhythms and sleep are correlated with the participation of immunological function to it [9]. Less sleep makes people tired and with low performance those people have 7 -8 hours daily sleep.…”
mentioning
confidence: 91%
“…In studies, biological restraint of IL-1 furthermore, TNF has been displayed to diminish NREM sleep, and height of IL-1 and TNF have been displayed to increment NREM sleep and lessen quick eye development (REM) sleep [10]. Under ordinary conditions, rest and the circadian mood guarantee a mitigating state during the daytime and a pro-inflammatory state during the evening [9]. Intense gentle resistant enactment increases NREM state of sleep and smothers REM state of sleep, though serious invulnerable reaction with an upsurge of cytokine levels causes rest aggravation with the concealment of both NREM and REM state of sleep [11].…”
mentioning
confidence: 99%
“…A resilient immune fitness (i.e., an adequate immune system) refers to the capacity to adapt to external health challenges by establishing an appropriate immune response to prevent or resolve diseases. Poor immune fitness is caused partly by genetic predisposition and personal characteristics such as age, sex, and underlying conditions, but it is also significantly impacted by lifestyle factors such as daily diet, (lack of) physical exercise, chronic stress, and poor sleep [ 3 , 4 , 5 ]. Recently, Kiani et al [ 6 ] evaluated the impact of reduced perceived immune fitness on the presence and severity of 2019 coronavirus (COVID-19) complaints.…”
Section: Introductionmentioning
confidence: 99%